A 2-year Comparative Analysis of Outcomes and Endovascular Interventions in Radio-Cephalic vs. Brachio-Cephalic Fistulae. (April 2023) - Fallon, John; Kirkham, Emily; Chana, Manik; Kulkarni, Sachin R.; Cooper, David; Paravastu, Sharath
Background: Arterio-venous fistulae are often compromised by complications, notably thrombosis. We assess the 2 year follow-up data of a cohort of patients from a single vascular centre in the UK who underwent BCF or RCF creation with the objective of assessing the outcome differences and intervention rates between fistula types. Materials and Methods: We retrospectively assessed a cohort of 195 patients who underwent creation of arterio-venous fistula (100 BCF, 95 RCF) between January 2016 and December 2018, following them up for 2 years assessing the outcomes and interventions on their AVFs. The outcomes assessed were primary and cumulative patency at 6 weeks, 6, 12 and 24 months. Multinomial logistic regression to account for confounding variables age, gender, procedure, side, anticoagulant, vessel size and co-morbidities was performed. A Kaplan-Meier analysis of time to endovascular intervention was also performed comparing RCF and BCF. Results: Cumulative patency rates for BCF vs RCF were 91% vs. 89% at 6 weeks ( X 2 (3, N = 194) = 4.70, P = .19), 83% vs. 76% at 6 months ( X 2 (3, N = 188) = 7.72, P = .05), 78% vs. 69% at 12 months ( X 2 (4, N = 175) = 5.37, P = .25) and 68% vs. 65% at 24 months ( X 2 (4, N = 161) = 5.24, P = .24). Endovascular intervention rate becomes divergent at 5 months, with the steepest difference between 6 and 12 months. Comparative endovascular intervention rates between BCF and RCF were 20% vs. 31% at 6 months, 41% vs. 40% at 12 months and 40% vs. 49% at 24 months. Conclusion: RCF seem to have significantly lower patency at 6 months and have higher endovascular intervention rates compared to BCF. A focussed surveillance protocol could prove effective in improving outcomes for RCF.